Preservation and Quality Evaluation of Sisnu (Urtica plaviflora) by Making Gundruk like Fermented Product - Mishra, Achyut; Kharel, Ganga Prasad (Journal of Food Science and Technology Nepal, 2013)
Sisnu (nettle buds) of variety Urtica plaviflora, an under explored herb of Himalayan region, was preserved by fermentation followed by drying process and quality was evaluated. Chemical analyses of fresh Sisnu was found to be 84.4% moisture, 3.64g crude protein, 4.15g ash, 1.66g fiber, 0.52g fat, 64.10mg potassium, 23.65mg calcium, 17.17mg Sodium and 32.12mg iron per 100g samples on dry basis. The protein and potassium contents were found approximately six times higher than other leafy vegetables. In fermented product, ash, calcium and potassium contents were decreased significantly (p<0.05). Fermentation was carried out as control, by adding 1% salt, 1% sugar and with the combination of 1% salt and 1% sugar. All fermented products have typical acidic flavor of Gundruk with additional putrid flavor. From the statistical analysis, color of the dried fermented products were significantly indifferent (p>0.05) but flavor and test of salt and or sugar added products were significantly different (p<0.05) from the control. J. Food Sci. Technol. Nepal, Vol. 6 (114-117), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8272